Effect of alkaline pretreatment on mesophilic and thermophilic anaerobic digestion of a submerged macrophyte: Inhibition and recovery against dissolved lignin during semi-continuous operation. (August 2017) - Koyama, Mitsuhiko; Watanabe, Keiko; Kurosawa, Norio; Ishikawa, Kanako; Ban, Syuhei; Toda, Tatsuki
Highlights: Long-term effect of alkaline pretreatment on AD of submerged macrophyte. Accumulation of dissolved lignin in the digestate of pretreated conditions. Temporal inhibition of CH4 production at mesophilic and thermophilic digestion. Recovery of CH4 production in both AD temperatures within 44–64 days. Higher improvement of CH4 recovery by pretreatment at lower AD temperature. Abstract: The long-term effect of alkaline pretreatment on semi-continuous anaerobic digestion (AD) of the lignin-rich submerged macrophyte Potamogeton maackianus was investigated using mesophilic and thermophilic conditions. In pretreated reactors, dissolved lignin accumulated to high levels. CH4 production under the pretreated condition was higher than that of the untreated condition, but decreased from Days 22 (mesophilic) and 42 (thermophilic). However, CH4 production subsequently recovered, although dissolved lignin accumulated. Further, the change in the microbial community was observed between conditions. These results suggest that dissolved lignin temporarily inhibited AD, although acclimatization to dissolved lignin occurred during long-term operation. During the steady state period, mesophilic conditions achieved a 42% increase in the CH4 yield using pretreatment, while thermophilic conditions yielded an 8% increment. Because volatile fatty acids accumulated even after acclimatization during the thermophilic pretreated condition and was discharged with the effluent, improvement of the methanogenic step would enable enhanced CH4 recovery.